THE PRAYER PATER SANCTE IN THE SYRIAN ORTHODOX BAPTISMAL LITURGY - Whitaker, E. C. (The journal of theological studies, 1977)
E. C. WHITAKER; THE PRAYER PATER SANCTE IN THE SYRIAN ORTHODOX BAPTISMAL LITURGY, The Journal of Theological Studies, Volume XXVIII, Issue 2, 1 October 1977, Pa